Obtaining and characterizing a concentrated water-soluble extract based on tarwi (lupinus mutabilis sweet) flavored with essences (Aporte Santiaguino, 2025)
The research consisted of developing a concentrated water-soluble extract of tarwi (Lupinus mutabilis Sweet) (CWSTE) flavored with essences. The experimental design had three stages. First: Perform physicochemical, microbiological, and functional analyses of the tarwi. Second: Conduct preliminary and definitive tests with the objective of finding a formulation for the development of a CWSTE similar to commercial products (almond beverage). Third: Characterize the final beverage. Optimization was carried out using a rotational central composite design with 22 treatments. Treatment (T2) was selected using sensory and physical evaluation, with the following results: dilution 1:2 (Tarwi: water), 0.016% carboxymethylcellulose, sediment height 0.02 m, density 1.021 kg/m, soluble solids 6, pH 5.67, appearance 9, flavor 7, color 8.5, odor 7.5, and yield 74.5%. This treatment was evaluated by 30 panelists using a 7-point hedonic scale, obtaining flavor, color, and appearance scores greater than 5, a p-value less than 0.05, and an odor score less than 5. This indicates that it was accepted by the panelists with a 95% confidence level. The proximate chemical analysis reported: protein 0.36%, carbohydrate 1.91%, fat 0.32%, energy 11.94 kcal, moisture 97.34%, and ash 0.08%. Microbiological results showed mesophilic aerobes < 1 mohos < 1 cfu/ml.  and coliforms < 3 NMP/ml. Antioxidant capacity (DPPH) was 11.9 umol ET/100g, and polyphenolics were 2.54 mgGAE/100g.
Keywords: Plant-based beverage; Tarwi; Lupin; Sensory analysis; Antioxidant capacity